„Pietismus ist Kommunikation.“ Historische Netzwerkanalyse der Korrespondenz Johann Christoph Martinis (1722–1732) - Lorene Heimerl (Historia.scribere)
“Pietism is Communication.” Historical network analysis of the correspondence of Johann Christoph Martini (1722–1732)